Deletion of pax7 changes the tunica muscularis of the mouse esophagus from an entirely striated into a mixed phenotype - Wörl, Jürgen; Breuer, Christian; Neuhuber, Winfried (Developmental Dynamics, 2009)
Keywords: Apoptosis; Muscle precursors; Esophageal myogenesis; Striated muscle; Satellite cells

Enteric co-innervation of esophageal striated muscle fibers: A phylogenetic study - Hempfling, Christina; Seibold, Ralf; Shiina, Takahiko; Heimler, Wolfgang; Neuhuber, Winfried; Wörl, Jürgen (Autonomic Neuroscience-Basic & Clinical, 2009)
Keywords: Esophagus; Fish; Bat; Enteric nervous system; Neuromuscular junction; Sheep; Frog; He-goat; Shrew; Antelope

Enteric co-innervation of striated muscle in the esophagus: still enigmatic? - Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2016)
The existence of a distinct ganglionated myenteric plexus between the two layers of the striated tunica muscularis of the mammalian esophagus has represented an enigma for quite a while. Although an enteric co-innervation of vagally innervated motor endplates in the esophagus has been suggested repeatedly, it was not possible until recently to demonstrate this dual innervation. Twenty-two years ago, we were able to demonstrate that motor endplates in the rat esophagus receive dual innervation from both vagal nerve fibers originating in the brain stem and from varicose enteric nerve fibers originating in the myenteric plexus. Meanwhile, a considerable amount of data has been gathered on enteric co-innervation and its occurrence in the esophagus of a variety of species including humans, its neurochemistry, spatial relationships on motor endplates, ontogeny and possible functional roles. These data underline the significance of this newly discovered innervation component, although its function in vivo is still largely unknown. The aim of this review, which is an update of our previous paper (Worl and Neuhuber in Histochem Cell Biol 123(2):117-130. doi:10.1007/s00418-005-0764-7, 2005a), is to summarize the current knowledge about enteric co-innervation of esophageal striated muscle and to provide some hints as to its functional significance.
EVALuna2:184248

Impact of Siponimod on Enteric and Central Nervous System Pathology in Late-Stage Experimental Autoimmune Encephalomyelitis - Weier, Alicia; Enders, Michael; Kirchner, Philipp; Ekici, Arif Bülent; Bigaud, Marc; Kapitza, Christopher; Wörl, Jürgen; Kuerten, Stefanie (International Journal of Molecular Sciences, 2022)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS). Although immune modulation and suppression are effective during relapsing-remitting MS, secondary progressive MS (SPMS) requires neuroregenerative therapeutic options that act on the CNS. The sphingosine-1-phosphate receptor modulator siponimod is the only approved drug for SPMS. In the pivotal trial, siponimod reduced disease progression and brain atrophy compared with placebo. The enteric nervous system (ENS) was recently identified as an additional autoimmune target in MS. We investigated the effects of siponimod on the ENS and CNS in the experimental autoimmune encephalomyelitis model of MS. Mice with late-stage disease were treated with siponimod, fingolimod, or sham. The clinical disease was monitored daily, and treatment success was verified using mass spectrometry and flow cytometry, which revealed peripheral lymphopenia in siponimod- and fingolimod-treated mice. We evaluated the mRNA expression, ultrastructure, and histopathology of the ENS and CNS. Single-cell RNA sequencing revealed an upregulation of proinflammatory genes in spinal cord astrocytes and ependymal cells in siponimod-treated mice. However, differences in CNS and ENS histopathology and ultrastructural pathology between the treatment groups were absent. Thus, our data suggest that siponimod and fingolimod act on the peripheral immune system and do not have pronounced direct neuroprotective effects.
CRIS-Team Scopus Importer:2022-12-09
Keywords: central nervous system; enteric nervous system; experimental autoimmune encephalomyelitis; fingolimod; multiple sclerosis; siponimod

Involvement of catecholaminergic neurons in motor innervation of striated muscle in the mouse esophagus - van der Keylen, Piet; Garreis, Fabian; Steigleder, Ruth; Sommer, Daniel; Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2016)
Enteric co-innervation is a peculiar innervation pattern of striated esophageal musculature. Both anatomical and functional data on enteric co-innervation related to various transmitters have been collected in different species, although its function remains enigmatic. However, it is unclear whether catecholaminergic components are involved in such a co-innervation. Thus, we examined to identify catecholaminergic neuronal elements and clarify their relationship to other innervation components in the esophagus, using immunohistochemistry with antibodies against tyrosine hydroxylase (TH), vesicular acetylcholine transporter (VAChT), choline acetyltransferase (ChAT) and protein gene product 9.5 (PGP 9.5), α-bungarotoxin (α-BT) and PCR with primers for amplification of cDNA encoding TH and dopamine-β-hydroxylase (DBH). TH-positive nerve fibers were abundant throughout the myenteric plexus and localized on about 14% of α-BT-labelled motor endplates differing from VAChT-positive vagal nerve terminals. TH-positive perikarya represented a subpopulation of only about 2.8% of all PGP 9.5-positive myenteric neurons. Analysis of mRNA showed both TH and DBH transcripts in the mouse esophagus. As ChAT-positive neurons in the compact formation of the nucleus ambiguus were negative for TH, the TH-positive nerve varicosities on motor endplates are presumably of enteric origin, although a sympathetic origin cannot be excluded. In the medulla oblongata, the cholinergic ambiguus neurons were densely supplied with TH-positive varicosities. Thus, catecholamines may modulate vagal motor innervation of esophageal-striated muscles not only at the peripheral level via enteric co-innervation but also at the central level via projections to the nucleus ambiguus. As Parkinson's disease, with a loss of central dopaminergic neurons, also affects the enteric nervous system and dysphagia is prevalent in patients with this disease, investigation of intrinsic catecholamines in the esophagus may be worthwhile to understand such a symptom.
EVALuna2:35349

Monoamines in the enteric nervous system - Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2018)
Recent advances in neurogastroenterology have extended and refined our knowledge on the roles monoamines play in physiology and pathophysiology of the gastrointestinal tract. The catecholamine noradrenaline, as the primary transmitter of postganglionic sympathetic neurons, orchestrates motility and secretory reflexes and controls arterial perfusion as well as immune functions. The catecholamine dopamine is produced by a subpopulation of enteric neurons which possibly use it as transmitter. Serotonin, largely produced by enterochromaffin cells and to a small extent by enteric neurons profoundly affects gut motility, enteric neuron development and is also involved in immunomodulation. However, its mode of action and the relative contribution of non-neuronal versus neuronal serotonin was recently subject to debate again. Histamine, although entirely of non-neuronal origin, is pivotal for gastrointestinal neuroimmunomodulation besides its paracrine effect in gastric HCl production.
EVALuna2:35201

Murine esophagus expresses glial‐derived central nervous system antigens - Kapitza, Christopher; Chunder, Rittika; Scheller, Anja; Given, Katherine S.; Macklin, Wendy B.; Enders, Michael; Kürten, Stefanie; Neuhuber, Winfried; Wörl, Jürgen (International Journal of Molecular Sciences, 2021)
Multiple sclerosis (MS) has been considered to specifically affect the central nervous system (CNS) for a long time. As autonomic dysfunction including dysphagia can occur as accompanying phenomena in patients, the enteric nervous system has been attracting increasing attention over the past years. The aim of this study was to identify glial and myelin markers as potential target structures for autoimmune processes in the esophagus. RT‐PCR analysis revealed glial fibrillary acidic protein (GFAP), proteolipid protein (PLP), and myelin basic protein (MBP) expression, but an absence of myelin oligodendrocyte glycoprotein (MOG) in the murine esophagus. Selected immunohistochemistry for GFAP, PLP, and MBP including transgenic mice with cell‐type specific expression of PLP and GFAP supported these results by detection of (1) GFAP, PLP, and MBP in Schwann cells in skeletal muscle and esophagus; (2) GFAP, PLP, but no MBP in perisynaptic Schwann cells of skeletal and esophageal motor endplates; (3) GFAP and PLP, but no MBP in glial cells surrounding esophageal myenteric neurons; and (4) PLP, but no GFAP and MBP in enteric glial cells forming a network in the esophagus. Our results pave the way for further investigations regarding the involvement of esophageal glial cells in the pathogenesis of dysphagia in MS.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Autoantibodies; Dysphagia; Enteric glia; Enteric nervous system; Esophagus; Glial fibrillary acidic protein; Motor endplate; Multiple sclerosis; Myelin basic protein; Proteolipid protein

Neurochemical classification of serotonin-immunoreactive neurons co-innervating motor endplates in the mouse esophagus - Zinsser-Krys, Jillena; Kapitza, Christopher; Böhnke, Lena; van der Keylen, Piet; Neuhuber, Winfried; Wörl, Jürgen (Anatomical Record, 2022)
Serotonin immunoreactivity was previously found in myenteric neurons co-innervating motor endplates in the mouse esophagus striated muscle and an involvement in motility control was suggested. However, it is not known if other neuroactive substances are present in these neurons and to what extent they co-localize. First, vasoactive intestinal peptide (VIP) was established as a bona fide marker for putative inhibitory myenteric neurons by evaluating co-localization with neuronal nitric oxide synthase (nNOS) and neuropeptide Y (NPY). Then, co-localization of serotonin and VIP was tested in co-innervating axons on motor endplates, which were visualized with α-bungarotoxin (α-BT) by multilabel immunofluorescence. Myenteric ganglia were also surveyed for co-localization in neuronal perikarya and varicosities. nNOS, NPY, and VIP were completely co-localized in enteric co-innervating nerve terminals on motor endplates. After co-staining with VIP, we found (a) serotonin (5-HT)-positive nerve endings without VIP (44% of 5-HT-positively innervated endplates), (b) 5-HT- and VIP-positive endings without co-localization (35%), and (c) 5-HT- and VIP-positive endings with co-localization (21%). About one-fifth of nerve terminals on motor endplates containing 5-HT originate from putative inhibitory peptidegic nitrergic neurons. However, the majority represents a different population presumably subserving different functions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: 5-hydroxytryptamine; enteric co-innervation; neuromuscular junction; neuronal nitric oxide synthase; neuropeptide Y; vasoactive intestinal peptide

Serotonin-immunoreactive neurons and mast cells in the mouse esophagus suggest involvement of serotonin in both motility control and neuroimmune interactions - Hempfling, Christina; Neuhuber, Winfried; Wörl, Jürgen (Neurogastroenterology and Motility, 2012)
Background Serotonin is a major transmitter in the gastrointestinal tract, but little is known about the serotonergic system in the esophagus. Methods The aim of this study was to use multilabel immunofluorescence to characterize serotonin-positive nerve cell bodies and fibers and their relationship with other neuronal and non-neuronal elements in the mouse esophagus. Antibodies against serotonin, vesicular acetylcholine transporter (VAChT), choline acetyltransferase (ChAT), protein gene product 9.5 (PGP 9.5), and alpha-bungarotoxin (alpha-BT), were used. Key Results Serotonin-containing perikarya represented similar to 10% of all PGP 9.5-positive myenteric neurons. Serotonin-positive varicose nerve fibers were found in the lamina muscularis mucosae and present on similar to 13% of alpha-BT-labeled motor endplates in addition to VAChT-immunoreactive motor terminals. As ChAT-positive neurons of the compact formation of the nucleus ambiguus were negative for serotonin, serotonin-positive varicosities on motor endplates are presumed to be of enteric origin. On the other hand, cholinergic ambiguus neurons were densely supplied with serotonin-positive varicosities. The tela submucosa and tunica adventitia contained large numbers of serotonin-positive mast cells, a few of which were in close association with serotonin-positive nerve fibers. Conclusions & Inferences The mouse esophagus is endowed with a rich serotonin-positive intrinsic innervation, including enteric co-innervation of striated muscles. Serotonin may modulate vagal motor innervation of esophageal-striated muscles not only at the central level via projections of the raphe nuclei to the nucleus ambiguus but also at the peripheral level via enteric co-innervation. In addition, mast cells represent a non-neuronal source of serotonin, being involved in neuroimmune processes.
Keywords: 5-hydroxytryptamine; enteric co-innervation; mast cell; myenteric neuron; neuromuscular junction; nucleus ambiguus